Secondary prevention of arterial hypertension in primary health care - Kurochka, V. L. (Zaporozhye Medical Journal, 2013)
Оn the example of «School of health» modern approaches to organization of treatment and prophylaxis help to population are proposed, which are directed on a primary link of heath protection system, on establishment of partnership between medical workers and patients, application оf the proper instructive program for hypertensive patients.